Effect of the proportion of stevia leaf extract (Stevia rebaudiana B) on the chemical characteristic properties of functional pudding - Mujianto, Mujianto; Zalizar, Lili; Damat, Damat; Relawati, Rahayu; Harahap, Burhanuddin; Iswahyudi, Iswahyudi; Sustiyana, Sustiyana (Institute for Research and Community Service (LPPM), Universitas Islam Madura, Indonesia, 2024)
Functional pudding, a popular dessert, has attracted attention in recent years due to its potential as a vehicle for delivering health-promoting ingredients. This study investigates the impact of different proportions of stevia leaf extract (Stevia rebaudiana B) on the physicochemical properties of functional pudding. Stevia leaf extract, known for its natural sweetness and negligible impact on blood sugar levels, holds promise as a low-calorie alternative to traditional sweeteners. Through systematic experimentation, various concentrations of stevia leaf extract are incorporated into pudding formulations, and their effects on water content, ash content, fat content, protein content, and carbohydrate content are evaluated. The results indicate significant alterations in the physicochemical characteristics of the pudding samples, with variations observed in water content, ash content, fat content, protein content, and carbohydrate content. Specifically, sample F6, containing the highest proportion of stevia leaf extract, exhibits notable changes, including a high-water content of 88.31%, low ash content of 0.49%, moderate fat content of 0.81%, elevated protein content of 5.35%, and reduced carbohydrate content of 5.02%. These findings underscore the potential of stevia leaf extract as a functional ingredient in pudding formulations and provide insights for the development of healthier dessert options.